Workforce attachment after a congenital long QT syndrome diagnosis: a Danish nationwide study. Issue 2 (6th July 2022) - Jespersen, Camilla H B; Butt, Jawad Haider; Krøll, Johanna; Winkel, Bo Gregers; Kanters, Jørgen K; Gislason, Gunnar; Torp-Pedersen, Christian; Bundgaard, Henning; Jensen, Henrik Kjærulf; Køber, Lars; Tfelt-Hansen, Jacob; Weeke, Peter E
Abstract : Objective: To examine workforce attachment among patients with congenital long QT syndrome (cLQTS) following diagnosis and identify factors associated with workforce attachment. Methods and results: In this nationwide cohort study, all patients diagnosed with cLQTS in Denmark between 1996 and 2016 aged 18–60 years at diagnosis were identified using nationwide registries. Patients attached to the workforce at diagnosis were included. Attachment to the workforce 1 year after cLQTS diagnosis was examined and compared with a background population matched 1:4 on age, sex and employment status. Multiple logistic regression was performed to identify factors associated with 1-year workforce detachment among patients with cLQTS. 298 patients fulfilled the inclusion criteria. Six months after cLQTS diagnosis, 90.9% of patients with cLQTS were attached to the workforce compared with 95.0% in the background population (p=0.006 for difference). One year after diagnosis, 93.3% of patients with cLQTS were attached to the workforce compared with 93.8% in the background population (p=0.26). Among patients with cLQTS, a severe cLQTS disease manifestation was associated with workforce detachment 1 year after diagnosis (compared with asymptomatic patients; aborted cardiac arrest OR 20.4 (95% CI, 1.7 to 249.9); ventricular tachycardia/syncope OR 10.9 (95% CI, 1.1 to 110.5)). No other associated factors were identified. Conclusions: More than 90% of patients with cLQTS remained attached to the workforce 1 year after diagnosis, which was similar to a matched background population. Patients with a severe cLQTS disease manifestation were less likely to be attached to the workforce 1 year after diagnosis.